A tumor suppressor Retinoblastoma1 is essential for embryonic development in the sea urchin. Issue 12 (1st October 2019) - Fernandez‐Nicolas, Ana; Xu, Derek; Yajima, Mamiko
Abstract: Background: Embryonic cells and cancer cells share various cellular characteristics important for their functions. It has been thus proposed that similar mechanisms of regulation may be present in these otherwise disparate cell types. Results: To explore how regulative embryonic cells are fundamentally different from cancerous cells, we report here that a fine balance of a tumor suppressor protein Retinoblastoma1 (Rb1) and a germline factor Vasa are important for proper cell proliferation and differentiation of the somatic cells during embryogenesis of the sea urchin. Rb1 knockdown blocked embryonic development and induced Vasa accumulation in the entire embryo, while its overexpression resulted in a smaller‐sized embryo with differentiated body structures. These results suggest that a titrated level of Rb1 protein may be essential for a proper balance of cell proliferation and differentiation during development. Vasa knockdown or overexpression, on the other hand, reduced or increased Rb1 protein expression, respectively. Conclusions: Taken together, it appears that Vasa protein positively regulates Rb1 protein while Rb1 protein negatively regulates Vasa protein, balancing the act of these two antagonistic molecules in somatic cells. This mechanism may provide a fine control of cell proliferation and differentiation, which is essential for regulative embryonic development. Key Findings: A tumor suppressor Rb1 is important for proper embryonic development of the sea urchin. Rb1 overexpression incompletely progresses and its knockdown compromises embryonic development. Rb1 knockdown results in excessive Vasa accumulation in the entire embryo. A fine balance of Rb1 and Vasa is critical for regulative embryonic development.